ADAPTATION OF EDUCATORS TO THE LABOR MARKET THROUGH SELF-DEVELOPMENT (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the issues of teachers’ adaptation to the modern labor market through self-development. The study highlights the importance of developing professional competencies, mastering digital technologies, applying innovative approaches, and continuous education processes. In addition, the factors for increasing teachers’ competitiveness and the prospects for professional growth are discussed in detail.
Keywords: Teacher, labor market, self-development, professional competence, innovative technologies, digital education, continuous education, pedagogical skills, competitiveness, modern education.